Evaluación del nivel conocimiento de los estudiantes de odontología, posgrado en endodoncia y especialistas sobre el proceso de desinfección de conos de gutapercha durante su práctica clínica. (2020)
Endodontics is an especiality of dentistry, and as usual, an aseptic environment is needed to avoid cross-contamination. One of the most important points are gutta-percha cones, since these are going to be inserted directly into the canal and are easy to be contaminated due to their manipulation: therefore, the present research is focused on evaluating knowledge in gutta-percha cone disinfection.